An Analysis on Teachers’ Professional Competence at SMP Muhammadiyah 3 Gending Probolinggo - Lufi Kartika Sari (Jurnal Kebijakan dan Pengembangan Pendidikan, 2014)
Lufi Kartika SariLecturer Language Center University of Muhammadiyah Malange-mail: loe_phie_sr@yahoo.comAbstract:This research used qualitative method. Based on the findings, 1) teachers’ professional competence was influenced by non-permanent teachers. They prioritize their main school instead of their subordinate school. It was proven by most of them teach carelessly, focused on textbooks and worksheets, do not develop teaching materials, copy and download teaching equipment; 2) school policies in SMP Muhammadiyah were based on government’s instruction. Some others were initiated by the principal regarding the school condition; 3). the most significant supporting factor was teachers’ main schools that held more trainings; 4) the inhibiting factors were fund, students, workforce, facilities, the evaluation of training, teachers’ personality, and school management, society which was non-Muhammadiyah; government prioritized public schools.Keywords: teachers’ professional competence, instructionAbstrak:Penelitian ini menggunakan pendekatan kualitatif. Dapatan kajian menunjukkan: 1) kompetensi profesional guru dipengaruhi oleh guru-guru tidak tetap. Mereka memprioritaskan tempat utama mengajar bukan. Hal ini terbukti dengan sebagian besar dari mereka mengajar sembarangan, berfokus pada buku pelajaran dan lembar kerja, tidak mengembangkan bahan ajar, dan hanya menggunakan peralatan mengajar dan tidak mengembangkannya, 2) kebijakan sekolah di SMP Muhammadiyah didasarkan pada instruksi pemerintah. Beberapa orang lain yang diprakarsai oleh kepala sekolah mengenai kondisi sekolah; 3). faktor pendukung yang paling signifikan adalah adanya pelatihan bagi guru; 4) faktor penghambat adalah dana, siswa, tenaga kerja, fasilitas, evaluasi pelatihan, guru, dan manajemen sekolah, masyarakat yang non-Muhammadiyah, dan sekolah negeri diprioritaskan.Kata kunci: kompetensi profesional guru, pembelajaran